Mallele Boyang Tradition and Mandar Culinary Heritage: Between Space, Taste, and Relations - Wijaya, Guntur Sekti; Lestari, Erawati Dwi (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study examines the short story Rumah Batu Kakek Songkok by Lina Pratica Wijaya using the theory of literary anthropology with a focus on the cultural setting of the Mandar ethnic group in West Sulawesi. The story portrays the everyday life of the Mandar people through the depiction of Mallele Boyang, a traditional communal practice of relocating a resident’s house to a new location involving the collective effort of many men from the community. This tradition is not merely a physical activity but also a manifestation of deeply rooted values of togetherness, solidarity, and kinship. Furthermore, the short story highlights the richness of traditional Mandar cuisine such as loka yanno (Mandar-style fried banana) and mung bean porridge which are shared with the community as a gesture of gratitude after the completion of the Mallele Boyang ritual. This research employs a descriptive qualitative method to analyze the cultural elements embedded in the literary text and interpret their meaning within the social context of Mandar society. The theory of literary anthropology serves as a bridge to understand the relationship between cultural representation in the text and the lived experiences of the indigenous community. The hypothesis proposed in this study is that Rumah Batu Kakek Songkok functions not only as a reflection of the local life and cultural values of the Mandar people but also as a cultural critique of the erosion of communal practices in modern society due to the rise of individualism. As such, this literary work becomes a vital medium for preserving traditional cultural values and reinforcing ethnic identity in contemporary Indonesian literature.